From Passion to Abyss: the Mental Health of Athletes during COVID-19 Lockdown - Pitacho, Liliana; Palma, Patrícia Jardim da; Correia, Pedro; Cordeiro, João Pedro Pina (My University, 2023)
The outbreak and pandemic of COVID-19 forced people into extreme isolation and social distancing, with significant limitations on various activity sectors, including sports. This study aimed to assess the psychological health status of athletes during sports lockdown. Additionally, we intend to verify the mediating role of sleep disorders in stress perception and subjective happiness. Our sample was composed of 1492 Portuguese athletes from eight different team sports. During sports lockdown, athletes were found to have high stress levels and low subjective happiness levels and experience sleep disorders. Finally, these results conclude that sports lockdowns harm athletes’ psychological health and well-being. Pay cuts to athletes are an extra stress factor that exacerbate these adverse effects on psychological health. Finally, sleep is a mediator variable between stress perception and subjective happiness levels. This study’s significant contributions, limitations, and future directions are discussed in the conclusion.
Keywords: Lockdown; Sport; Stress; Sleep disorders; Subjective happiness; Mental health; Pay cuts